Perception on quality of life among community in Selangor - Mohamed Osman, Mariana; Rosli, Nur Farhanah; Rabe, Noor Suzilawati (2017)
The quality of life (QOL) is a subjective matter that diversely defined by scholars. Since 1930s researchers from various fields have expressed an interest in the definition of QOL including of investigating and measuring of QOL using different methods. Over the last four decades, Malaysia has made remarkable achievements regarding its economic growth as well as its socio-economic development. Numerous factors have been identified that may affect the quality of life of people according to their personal preferences. For example, the quality of the individual work as an engineer may differ with the quality of life of an individual work as a teacher. Nevertheless, how the individual itself measures the quality of life can be different between each other. However, definitions of quality of life are as numerous and inconsistent as the methods of assessing it. This paper highlights the perception towards the quality of life for the community lives in the state namely Selangor. For that, research question for the study comprises of question-related to what is the living condition of the population in Selangor and what is their satisfaction level towards the current living condition. To answer the question, research objectives are identified which are: to identify the current living condition in Selangor and to perceive the level of satisfaction towards the living condition in the State besides to provide a recommendation to have a good quality of life. There are four methodology stages are involved in this study and the method used is quantitative research that involved a participation of 500 respondents living in Selangor. The preliminary outcome of the study indicates that the community in Selangor measured their quality of life differently based on their socio-economic background. Also, several indicators and action were highlighted by the community to be considered as part of the recommendation to improve the current living standard towards a better quality of life in Selangor.